PENGARUH PROFESIONALISME, MOTIVASI DAN PENGAWASAN DENGAN KINERJA GURU SMP NEGERI KECAMATAN MAPILLI - Muhammad Alwi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2021)
This research have a purpose (1) to know the existence of influence which [is] Professionalism signifikan with performance learn SMP Country District of Mapilli; (2) to know the existence of influence which [is] signifikan Motivate with performance learn SMP Country District of Mapilli; (3) to know the existence of influence which is observation signifikan with performance learn SMP Country District of Mapilli; and (4) to know the existence of influence with which is signifikan between Professionalism, Motivation, and observation with performance learn SMP Country District of Mapilli. Population in research is teacher of SMP Country exist in District of Mapilli with amount of its population equal to 50 teacher. In this research of sampel the taken is entire/all teacher of SMP Country District of Mapilli, so that this research of meruapakan research of population. Technique analyse data by using Multiple Regression Linear of Analys: Tabulation of data, Assumptions of Multiple Regression and Examination of Hypothesis Research. Result of data analysis is: 1) professionalism level have an effect on postitif to make-up of teacher performance.This matter of indication that high lower him mount professionalism had unidirectional with yielded performance storey;level 2) Motivational level have an effect on postitif to make-up of teacher performance 3) Mount observation have an effect on postitif to make-up of teacher performance. This matter of indication that high lower unidirectional done/conducted observation intensity him with performance storey; level which is yielded. 4) Professionalism, observation and motivation by simultan have an effect on to make-up of teacher performance.